(untitled) (Third Sector Social Economic Review, 2019)
The aim of this study is to reveal the thoughts, perceptions and perspectives of the people living in Osmaniye about asylum seekers and refugees. For this purpose; education-health, security, citizenship and employment, It consists of four main headings and sub-problems under these headings. Qualitative research method was used in order to be suitable for the research purpose. The research data were collected using semi-structured interview technique within the framework of the basic and sub-problems of the research. In this context, face-to-face interviews were conducted with 17 individuals living in the central districts of Osmaniye where foreign migrants live. Within the scope of the interviews conducted, the public considers asylum seekers and immigrants as a security threat and it is found that they consider them as the reason for the increase in some social problems. They do not want the children of asylum seekers and refugees with their children to be educated in local schools. They expressed that they do not find each other’s negative behaviors appropriate because they are people of different cultures in terms of their role models and damaging their social development. It is also said that these migrants and refugees have changed in the social structure of Osmaniye.